Has Ukrainian business benefited from the adoption of the deep and comprehensive free trade area with the European Union? - Meteiko, Vitalina; Shapran, Ludmila (My University, 2019)
In general, changes in trade and economic relations with the EU have positive impact on Ukrainian industrial enterprises but businesses could benefit more if there was an effective government strategy in export promotion.
Keywords: Ukrainian industrial enterprises; EU market; benefits and problems; українські промислові підприємства; ринок Європейського Союзу; переваги та недоліки; кафедра ділової іноземної мови та міжнародної комунікації